Baseline Assessment of 25-Hydroxyvitamin D Reference Material and Proficiency Testing/External Quality Assurance Material Commutability: A Vitamin D Standardization Program Study. (22nd November 2019) - Phinney, Karen W; Sempos, Christopher T; Tai, Susan S-C; Camara, Johanna E; Wise, Stephen A; Eckfeldt, John H; Hoofnagle, Andrew N; Carter, Graham D; Jones, Julia; Myers, Gary L; Durazo-Arvizu, Ramon; Miller, W Greg; et al.
Abstract: The Vitamin D Standardization Program (VDSP) coordinated a study in 2012 to assess the commutability of reference materials and proficiency testing/external quality assurance materials for total 25-hydroxyvitamin D [25(OH)D] in human serum, the primary indicator of vitamin D status. A set of 50 single-donor serum samples as well as 17 reference and proficiency testing/external quality assessment materials wereanalyzed by participating laboratories that used either immunoassay or LC-MS methods for total 25(OH)D. The commutability test materials included National Institute of Standards and Technology Standard Reference Material 972a Vitamin D Metabolites in Human Serum as well as materials from the College of AmericanPathologists and the Vitamin D External Quality Assessment Scheme. Study protocols and data analysis procedures were in accordance with Clinical and Laboratory Standards Institute guidelines. The majority of the test materials were found to be commutable with the methods used in this commutability study. These results provide guidance for laboratories needing tochoose appropriate reference materials and select proficiency or external quality assessment programs and will serve as a foundation for additional VDSP studies.